Diseño de una guía multimedia de la música popular ecuatoriana e intérpretes salcedenses, mediante aplicaciones audiovisuales para la difusión de este género en el cantón Salcedo periodo 2014 - 2015 - Sangucho Taco, Franklin Patricio (2016)
This thesis project named: “DESIGN OF A MULTIMEDIA GUIDE ABOUT ECUADORIAN POPULAR MUSIC AND INTERPRETERS FROM SALCEDO, THROUGH AUDIOVISUAL APPLICATIONS FOR SPREADING THIS GENRE AT SALCEDO CANTON, 2014 - 2015 PERIOD.” aims to introduce the artists from Salcedo in an original and striking way; it means, a guide which contains information about each artists who live in Salcedo Canton. Regarding to the development of the proposal in writing, the thesis is divided into three chapters: the first chapter contains basic concepts of graphic design, layout, multimedia and interactivity; themes which are key issues for the development of the proposal, which are mentioned in the theoretical framework, while the second chapter supported the project by survey applied to Salcedo Canton inhabitants; and interviews targeting to the same artists from Salcedo involved in the Ecuadorian popular music and the people involved directly and indirectly in the proposal, too. Finally….